2016
DOI: 10.1016/j.toxrep.2016.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hecogenin on DNA instability

Abstract: Hecogenin is a sapogenin found in Agave species in high quantities and is responsible for the many therapeutic effects of these medicinal plants. In addition, this compound is also widely used in the pharmaceutical industry as a precursor for the synthesis of steroidal hormones and anti-inflammatory drugs. Despite Hecogenin being widely used, little is known about its toxicological properties. Therefore, the present study aimed to investigate the cytotoxic, genotoxic and mutagenic effects of Hecogenin on HepG2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The result revealed that cell treated with hecogenin, no cytotoxic effect was observed on HepG2 cells in 10 μm and 50 μm concentrations range. Furthermore, exposure of cells to 100 μm of hecogenin demonstrated a slight reduction in cell viability, whereas treatments with concentration above than 100 μm, cell viability decreased significantly by 30% [49] ( fig. 8).…”
Section: Anti-cancer Role Of Hecogeninmentioning
confidence: 93%
See 1 more Smart Citation
“…The result revealed that cell treated with hecogenin, no cytotoxic effect was observed on HepG2 cells in 10 μm and 50 μm concentrations range. Furthermore, exposure of cells to 100 μm of hecogenin demonstrated a slight reduction in cell viability, whereas treatments with concentration above than 100 μm, cell viability decreased significantly by 30% [49] ( fig. 8).…”
Section: Anti-cancer Role Of Hecogeninmentioning
confidence: 93%
“…In this study they have prepared thirty three analogs and tested on various in vitro (cell proliferation, cytotoxicity assay, lactate dehydrogenase release assay, migration assay, invasion assay, protein extraction and immunoblotting assay) and in vivo model (orthotopic xenograft model by using MDA-MB-231/GFP human breast cancer cells), among which hecogenin 12-(30-methylphenyl thiosemicarbazone) have demonstrated the most potent antiproliferative, anti-migratory and anti-invasive activities at low concentration level [18]. Cruz et al, (2016) have reported that cytotoxic, genotoxic and mutagenic effects of hecogenin on HepG2 cells. Hecogenin cytotoxicity was studied by performing MTT assay.…”
Section: Anti-cancer Role Of Hecogeninmentioning
confidence: 99%